Self-healing of GaAs nanowires: An atomistic study - Wang, Jun; Lu, Chunsheng; Wang, Q.; Xiao, P.; Ke, F.; Bai, Y.; Shen, Y.; Wang, Y.; Chen, B.; Liao, X.; Gao, H. (Nil, 2012)
Fractured GaAs nanowires (NWs) with a zinc-blende structure can spontaneously self-heal throughout Ga–As re-bonding at fracture sites. In this paper, a systematic molecular dynamics study has been made with focus on the influence of lateral dimensions of GaAs NWs, multiple fractures and atomistic diffusion on the self-healing process. The results show that, as the lateral dimension increases from 2.31 to 9.23 nm, GaAs NWs lose their 46.0% capacity of self-healing. After 24 repeated cycles of fracture, the restored tensile strength of a NW reduces by 64.4%. Atomistic diffusion enhances the healing efficiency by eliminating mismatch of atoms.